Association of Family History, Body Mass Index, and Exercise Regularity with HbA1c Status in Type 2 Diabetes Melitus Patients - Aisyah, Riandini; Prabowo, Nurhasan Agung (Universitas Muhammadiyah Semarang, 2025)
Background: Urban life, especially in Surakarta, is easy to access and full of high-carbohydrate food and drink. This has increased unhealthy behavior and diets. The prevalence of diabetes Mellitus (DM) in Surakarta is growing, reaching 24% in 2021. Physical exercise and poor diet are important risk factors for DM, coupled with genetics, causing obesity. HbA1c levels periodically assess DM patients' glycemic management.Objective: This study aims to determine the association between family history, body mass index, and regular exercise with HbA1c status in type 2 DM patients at UNS Surakarta Hospital.Methods: The research was an observational study; 24 patients diagnosed with type 2 DM were recruited from the outpatient clinic of Universitas Sebelas Maret Hospital, Surakarta, Indonesia, in October 2021. Measurements were conducted to determine their HbA1c level by enzymatic methods and body mass index by measuring body weight and height, and they were questioned regarding their physical exercise and family history of diabetes. The data collected were analyzed using multiple logistic regression to ascertain the association between family history, body mass index, and exercise regularity with HbA1c status.Results: The findings indicated no statistically significant association between genetic background, body mass index, and exercise frequency with HbA1c status (p>0.05).Conclusion: This research shows that genetic history, body mass index, and exercise regularity are not associated with HbA1c status in type 2 DM in included subjects.